(3JMQjQ ebGdI GQTejOS aj JcSjQ GdOGFQIs - (3GQTejOSs
(3ChdgG (B:s
(3ebGdI GQTejOS aj JcSjQ GdOGFQI hgj KdGKI CTcGd aj cd OGFQI agj eSGhjI deKdK bGFe GdRGhjI s
(3BNQgG (B:s
(3YcS GdQgGf GdebOe dCfg ef GWdYI GdeMjW s
(3Vef eLehY , JQJjHgG (B: 3s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3GjGUhajG (B(1760) s
Keywords: (3eJaQbGJs